Advertisement from the sociolinguistic interface (In Asiry’s poems as an example) - Abdulrahman Karim, Aso; Muhmad Garib, Dilshad (Zanco Journal of Human Sciences, 2023)
The research is marked by (Advertisement from the sociolinguistic interface in Asiry's poems as an example), and the research consists of two researchers. The first research deals with a theoretical aspect, including the definition of social linguistics, the duties of language and its impact on the environment, and then some aspects of application. The second research includes the applied aspect of the poetry of The Asiry from the point of view of sociolinguistics.